SISTEM INFORMASI LAPORAN KEUANGAN PADA CV. ACEH RAYA BANDA ACEH - Rohama; Lukman Ahmad; Harry Idwan (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2022)
CV. Aceh Raya Banda Aceh is a company engaged in the contractor and supplier sector which has a large number of transactions both from purchasing and project management, but recording transactions that occur every day still uses the manual method, this sometimes makes financial reports with various types of transactions seem sluggish to the owner, the author only discusses the problem of the Financial Report Information System on the CV. Aceh Raya Banda Aceh using web-based. The research objective was to identify and design a financial reporting information system at CV. Aceh Raya Banda Aceh web-based. The collection of data needed in writing this research was obtained by two methods, namely literature studies related to library books and other scientific works, field studies by carrying out interviews and direct observation of objects related to this research as well as the system development method. used is the waterfall method. Financial Report Information System on CV. Aceh Raya Banda Aceh is carried out by one of the administrative staff and assisted by 2 (two) administrative staff in the field of administration to record and input transaction data. From the results of the study it can be concluded that the Financial Report Information System at CV. Aceh Raya Banda Aceh has followed the procedures and used a computer with a web-based programming language and MySQL as the database